Go-carting vehicles with electric drive. Issue 1 (September 2020) - Guskov, A
Abstract: The article describes a number of technical solutions that made it possible to develop Russia's first electric car for domestic go-cart racing, with a power reserve of 40 minutes of active driving, acceleration from 0 to 60 km / h in 9.5 seconds, with the ability to reverse, with functions energy recovery during braking. As battery cells, lithium-iron-phosphate cells were used. The article provides a calculation of the optimal battery capacity, based on the requirements for the mass-overall performance of the machine. The results of test runs of a serial model of cars with a power of 5 and 10 kW are presented. The calculations of the economic payback of a go-cart club equipped with electric traction machines are presented. The E-Cart, developed by teachers and undergraduates of the Department of "Automated electric drive" of the South Ural state University, has high performance characteristics. The technical solutions made it possible to achieve high acceleration dynamics and a range of 30 km. on a single charge, the "evenness" of the machines-the range of speed and torque when the battery charge level is from 15 to 100%.